A Value-Adding Approach To Reliability Under Preventive Maintenance Costs and Its Applications - Dubey, Rameshwar; Kılıç, Erdem; Ali, Sadia Samar; Weber, Gerhard Wilhelm (Taylor & Francis Ltd, 2014)
No equipment (system) can be perfectly reliable in spite of the utmost care and best efforts on the part of the designer, decision-maker and manufacturer. The two sides of maintenance are corrective and preventive maintenance. It is generally assumed that a preventive maintenance action is less costly than a repair maintenance action. We examine this proposition in detail on the basis of a failure-time model that relates conformance quality to reliability. Illustratively, we present reliability in the context of contracts with asymmetric information. The model shows how to overcome information rents through price distortions and quantity rationing. The paper ends with a conclusion and an outlook to future studies.
Keywords: Operational research; Financial means; Reliability function under preventive maintenance; Manufacturing services; Economics